1991
DOI: 10.1002/jat.2550110308
|View full text |Cite
|
Sign up to set email alerts
|

Site of action of grayanotoxins in mad honey in rats

Abstract: Grayanotoxins are known to occur in honey produced from the nectar of Rhododendrons of the family Ericaceae. Grayanotoxins extracted from honey sample obtained from a patient who experienced severe bradycardia and hypotension after ingesting two tablespoonfuls corresponded to Rhododendron ponticum tetrades. Anaesthetized albino rats were injected with honey extract intracerebroventricularly or intraperitoneally. The intracerebroventricular dose was equivalent to 50 mg honey and i.p. doses were equivalent to 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1
10

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 9 publications
0
43
1
10
Order By: Relevance
“…This finding is in agreement with the more severe cardiac findings in patients with a higher ingestion of honey in clinical series. Some experimental studies have reported that grayanotoxin also has a suppressive effect on respiratory functions (8,14). Although, in our study, respiratory frequency increased toward the end of the experiment in comparison to baseline values in animals administered high doses of GTX-III, this rise was not statistically significant.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…This finding is in agreement with the more severe cardiac findings in patients with a higher ingestion of honey in clinical series. Some experimental studies have reported that grayanotoxin also has a suppressive effect on respiratory functions (8,14). Although, in our study, respiratory frequency increased toward the end of the experiment in comparison to baseline values in animals administered high doses of GTX-III, this rise was not statistically significant.…”
Section: Discussioncontrasting
confidence: 91%
“…Some cases proceed with mild symptoms, such as nausea, vomiting, dizziness, and low blood pressure, but cases of complete block and asystole have also been reported (10,12). GTX can affect the central nervous system, skeletomuscular system, respiratory system, heart, and peripheral nervous system (8,13). In an experimental study, Onat et al showed the effects of GTX on the respiratory system, central nervous system, and peripheral nervous system by inducing bradycardia and respiratory depression in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrıca, GT II'de sinoatriyal noda spontan atımı baskılama özelliğine sahiptir. 10 GT' ler hücre membranlarındaki sodyum kanallarına bağlanarak etkilerini gösterir. Hücre membranlarındaki sodyum kanal geçirgenligini artı-rır, hücre membranında sodyum geçirgenliğinin artmasıyla repolarizasyon inhibe olur ve hücre membranı depolarizasyon süresi uzar.…”
Section: Discussionunclassified
“…In the literature, high doses of Grayanotoxin have been reported in samples collected from patients that consumed two table spoons of mad honey and that were subsequently diagnosed with severe bradycardia and hypotension (4). This kind of honey, mostly produced in the Black Sea region of Turkey, is considered a healing honey and may not cause toxic effects in every consumer.…”
Section: Discussionmentioning
confidence: 99%